Fenofibrate modulates inflammatory mediators as well as cross-talk between Trypanosoma cruzi- infected cardiomyocytes and fibroblasts - Sequeyra, Aldana Soledad (2021)
Chronic chagasic cardiomyopathy is characterized by parasite persistence, chronic inﬂammation and cardiac cell (Mc) death that may end lead to fbrosis and cardiac insuffciency. Activated fbroblasts (Fb) are involved in this process. Previous results from our group show that fenonofbrate (Fen), a PPARalpha ligand, modulates the expression of inﬂammatory mediators, prevents fbrosis and restores cardiac function in Trypanosoma cruzi (Tc) -infected mice. To deepen into the knowledge of the role of Mc and Fb in these events, in the present work we used an in vitro model of neonatal murine cardiac cells. We studied the modulator role of Fen on the inﬂammatory response of Mc and Fb infected with Tc. Mc and Fb were characterized by the expression of troponin C and s alpha-SMA, respectively, using Western blot (Wb). Wb and RT-qPCR analysis showed that Tc stimulated the expression of pro-inﬂammatory and pro-fbrotic enzymes like NOS2 and MMP-9 in Mc and Fb, whereas treatment with Fen (100µM) inhibited such expression in both cell lineages. In addition, after 48 h of infection we observed increased expression of CTGF, MMP-2 and TGF-beta by RT-qPCR in Mc and Fb, whereas Fen inhibited such increment (p<0.05). Besides, the rise of TNF-alpha and IL-6 after 2 to 6h of infection was precluded by Fen. Furthermore, while NFkB was activated at 30 min post-infection in Mc and Fb since cytoplasmic IkBalpha was signifcantly reduced as determined by Wb, treatment with Fen precluded such activation. Finally, the ability of Mc- and Fb -conditioned media to promote the expression of NOS2 in Fb and Mc was analyzed. Both media induced the expression of NOS2 in Fb and Mc while Fen inhibited its expression as assessed by Wb. These results emphasize the role of Mc and Fb in the inﬂammatory and pro-fbrotic response to Tc and the interaction between these cell lineages that Fen is able to modulate.